Data Mining Menggunakan Algoritma K-Means dengan Weka Interface untuk Klasterisasi Dosen Yang Memiliki Jabatan Fungsional pada Perguruan Tinggi Swasta dilingkungan LLDikti Wilayah III - Noviyanto Noviyanto; Prita Ekasari (Paradigma - Jurnal Komputer dan Informatika, 2022)
Permanent lecturers and lecturers who have functional positions absolutely must be owned by every university in Indonesia in order to fulfill the provisions of the legislation. Article 48 paragraph (2) of Law Number 14 of 2005 concerning Teachers and Lecturers states that the level of academic positions of permanent lecturers consists of asisten ahli, lektor, lektor kepala dan profesor. Lecturers still have to comply with these rules by submitting proposals for functional positions if they fulfill the qualification, in addition, universities where lecturers work must also proactively encourage lecturers to fulfill their obligations. Many lecturers from various universities, even though they have fulfill qualification, did not immediately take the initiative to propose their functional positions. In grouping the data for permanent lecturers and lecturers who have functional positions using data mining techniques, the k-means clustering method. The data is taken from the link https://pddikti.kemdikbud.go.id/. The results of this study are clusters of the number of permanent lecturers and lecturers who have functional positions into 3 clusters. There are 15 private universities (PTS) in the LLDikti III region with clusters of permanent lecturers and lecturers who have the most functional positions, then the medium level cluster is 45 private universities and the lowest cluster is 228 private universities.